Pharmaceutical cocrystals: walking the talk - Bolla, Geetha; Nangia, Ashwini (Chemical Communications, 2016)
Pharmaceutical cocrystals belong to a sub-class of cocrystals wherein one of the components is a drug molecule (or an active pharmaceutical ingredient, API) and the second is a benign food or drug grade additive (generally regarded as safe, GRAS). The two components are hydrogen-bonded in a fixed stoichiometric ratio in the crystal lattice. In the past decade, pharmaceutical cocrystals have demonstrated significant promise in their ability to modify the physicochemical and pharmacokinetic properties of drug substances, such as the solubility and dissolution rate, bioavailability, particle morphology and size, tableting and compaction, melting point, physical form, biochemical and hydration stability, and permeability. In this feature review, we highlight some prominent examples of drug cocrystals which exhibit variable hardness/softness and elasticity/plasticity depending on coformer selection, improvement of solubility and permeability in the same cocrystal, increase of the melting point for solid formulation, enhanced color performance, photostability and hydration stability, and a longer half-life. Cocrystals of flavanoids and polyphenols can make improved pharmaceuticals and also extend to the larger class of nutraceuticals. The application of crystal engineering to assemble ternary cocrystals expands this field to drug-drug cocrystals which may be useful in multi-drug resistance, mitigating side effects of drugs, or attenuating/enhancing drug action synergistically by rational selection. The advent of new techniques for structural characterization beyond the standard X-ray diffraction will provide a better understanding of drug phases which are at the borderline of crystalline-amorphous nature and even newer opportunities in the future.